ANATOMICAL CHARATERISTICS OF ARACEAE FAMILY IN LIWA BOTANICAL GARDEN, WEST LAMPUNG, LAMPUNG - Putri Kendari; Sri Wahyuningsih; Yulianty Yulianty; Martha Lulus Lande (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2020)
Indonesia is one of the countries with high Araceae diversity, which is about  36 genera consisting of 669 species. However research on the characteristics of Araceae in Indonesia is still limited. The existence of Araceae in Liwa Botanical Garden has not been studied. One of the characteristics in assessing plant diversity is anatomical features. Therefore, the aim of this study is to determine the anatomical characteristics of Araceae in Liwa Botanical Garden. This research was conducted from October to November 2019 in Liwa Botanical Garden, West Lampung, Lampung using the cruise method (Cruise Method). Araceae plants that are found identified in the Botany Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Lampung. The anatomical features of the leaves and petioles of Araceae was studied carefully. The results of this study indicate that each type of Araceae plant has different characteristics of epidermal cell structure and stomata. The characteristic shape of the epidermal cells is upright, while the characteristic shape of the stomata is amphibrachyparacitic. A certain types of Araceaeshows s a special characteristic which is having secretory cells.